Soul Dimension and Antithesis of Ibnu Sina’s Reincarnation Concept - Sofia, Naila; Soleh, Achmad Khudori (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2022)
Ibn Sina, the father of early modern medicine, had an unusual psychological concept. He has a different concept about the soul and reincarnation from the other physician. This study examines Ibn Sina's concept of the soul and his views on reincarnation. The research is based on literature data and uses qualitative methods. The results showed that Ibn Sina divided the human soul into three parts: plant, animal, and human. The human soul is eternal. That is, the soul does not decay after death, after separation from the body. The soul lives on in its realm. After death, the soul does not need a new body for its activities. Therefore, there is no reincarnation for the soul, and Ibn Sina disagrees with the concept of soul reincarnation by Aristotle